The effect of performance management on service quality through public satisfaction at the Medan City Population and Civil Registration Office - Lase, Zufilman; Rambe, Saima; Dewi, Ratna Sari (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study discusses the influence of performance management on the service quality of the Department of Population and Civil Registration of Kota Medan. This study consists of two variables, namely the Independent Variable (X) Performance Management and the Bound Variable (Y) Service Quality. The purpose of this study was to determine how big the influence of performance management on the service quality of the Department of Population and Civil Registration of Kota Medan. This research was conducted at the Department of Population and Civil Registration Kota Medan. The population of this study were the employees of the Department of Population and Civil Registration of Kota Medan, amounting to 32 people. So the research sample is 48 people, if the subject is less than 100, all can be taken so that the research is a population study. Furthermore, if the subject is more than 100 it can be taken 10-15% or more. So the sample of this study amounted to 32 people (all populations were sampled). The method used in this study is a quantitative method. Data collection techniques in this study are observation, interviews (interviews), questionnaires (questionnaires), literature studies and documentation studies. The data analysis technique used product moment correlation and hypothesis significance test. To determine the significant level of the influence of performance management on the service quality of the  kota Mean. Population and Civil Registration Service, a hypothesis test was carried out on r by determining the 5% significance level. Determine the test r table n=32. It is known based on data processing that the result of the r value of the product moment table with n = 32 and the 95% confidence level or 5% error is 0.284 and the r count is 0.40. Thus that r count 0.40 > r table 0.284. This means that there is a big influence between Performance Management and Service Quality. Thus the proposed hypothesis can be accepted, namely the magnitude of the influence of performance management on the service quality of the Kota Medan. Population and Civil Registration Service. Keywords: Performance Management, Service Quality